Long‐term therapy of multiple basal cell carcinomas: Clinicodermoscopic score for monitoring of intermittent vismodegib treatment. Issue 6 (17th October 2019) - Tognetti, Linda; Cinotti, Elisa; Fiorani, Diletta; Couzan, Caroline; Cavarretta, Camilla; Chazelle, Marie; Labeille, Bruno; Pianigiani, Elisa; Cevenini, Gabriele; Perrot, Jean L.; Rubegni, Pietro
Abstract: Vismodegib treatment of multiple basal cell carcinomas (BCCs) is limited by adverse effects and high relapse rates: intermittent regimens are therefore preferred for long‐term administration. The objective of this study was to investigate clinical and dermoscopic changes in BCCs during long‐term intermittent treatment and to identify those most indicative of tumor persistence/clearing. Clinical and dermoscopic images ( n = 380 each) of 38 BCCs were acquired at 10 observation times (t0–t9). Biopsies were performed at baseline (t0) and after 72 weeks of treatment (t9). All images were evaluated retrospectively by experts who assessed the presence/absence of 12 clinical and 14 dermoscopic features: clinical scores (CScs) and dermoscopic scores (DScs) were then calculated.